2017
DOI: 10.3389/fcimb.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Restriction Protein, KlcAHS, Promotes Dissemination of Carbapenem Resistance

Abstract: Carbapenemase-producing Klebsiella pneumoniae (KPC) has emerged and spread throughout the world. A retrospective analysis was performed on carbapenem-resistant K. pneumoniae isolated at our teaching hospital during the period 2009–2010, when the initial outbreak occurred. To determine the mechanism(s) that underlies the increased infectivity exhibited by KPC, Multilocus Sequence Typing (MLST) was conducted. A series of plasmids was also extracted, sequenced and analyzed. Concurrently, the complete sequences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The Pac_ICEs and plasmids may be able to evade restriction, in part because they are transferred as single stranded molecules. In addition, horizontally transferred mobile elements such as ICE or plasmids may avoid restriction through the presence of anti-restriction proteins 37 , 38 . In numerous cases of the acquisition of the R-M systems, it is possible to determine a potential probable source of the horizontal transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The Pac_ICEs and plasmids may be able to evade restriction, in part because they are transferred as single stranded molecules. In addition, horizontally transferred mobile elements such as ICE or plasmids may avoid restriction through the presence of anti-restriction proteins 37 , 38 . In numerous cases of the acquisition of the R-M systems, it is possible to determine a potential probable source of the horizontal transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of bla KPC-2 can be mediated by different molecular mechanisms, but the factors contributing to the epidemiological success of KPC-producing K. pneumoniae clonal complex (CC) 258 is unclear [ 13 ]. Recently, Liang et al [ 14 ] found that the KPC-2-producing ST11 K. pneumoniae can code an anti-restriction protein KlcA HS , which may help prevent the host bacteria from recognizing and incising foreign DNA by disrupting the restriction modification (RM) systems. The strains in this study also have bla KPC-2 and KlcA HS simultaneously (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their plasticity, part of the success of these bla KPC plasmids may also be attributable to the presence of toxin-antitoxin plasmid addiction systems ( ccdA / ccdB n=4 bla KPC plasmids; higA n=6; vapB/vapC n=11); anti-restriction mechanisms ( klcA n=16, previously shown to promote bla KPC dissemination(22)); and heavy metal resistance ( terB [tellurite] n=3; ars operon [arsenicals] n=3; chromate resistance n=1; cop operon/ pcoC / pcoE [copper] n=7; mer operon [mercury] n=10).…”
Section: Resultsmentioning
confidence: 99%